Contribution to the assessment of the Ecoplata programme for Integrated Coastal Zone Management (Uruguay) - Juan Adolfo Chica Ruiz; María Luisa Pérez-Cayeiro (Boletín de la Asociación de Geógrafos Españoles, 2016)
Although in the last two decades numerous programmes on different scales have been launched on Integrated Coastal Zone Management (ICZM) around the world, very few have had an evaluation to assess the degree of progress in the management model. This study has two fundamental objectives: the first of which is to contribute to the spreading of the iniciatives of integrated management´s most interesting coastal areas in Iberoamérica, known as the Ecoplata Program (Uruguay). The second objective is to do an evaluation of the planning and implementation of that program, this process of long-term ICZM is not without its challenges and opportunities.